PLAY IN COGNITIVE DEVELOPMENT IN TRANSITIONAL CHILDREN - María Paulina Ríos González; Andrés Iván Urrutia Mosquera (DIALÉCTICA, 2026)
The transition stage of early childhood education is fundamental to children’s comprehensive development, encompassing their cognitive, emotional, and psychosocial aspects. In early childhood, play plays a crucial role in learning, as through play, children explore, experiment, and create knowledge spontaneously and meaningfully. This essay-style article aims to analyze the impact of play on cognitive development in children in transition, highlighting its impact on processes such as memory, attention, creativity, and problem-solving. A qualitative approach with an interpretive paradigm is used for the methodological development, given the documentary nature that guides this article. The method will include a documentary review of studies conducted over the last five years in Colombia. A literature review will then be conducted, reflecting on the role of play in children’s comprehensive development and cognitive processes, providing theoretical and practical evidence on its pedagogical relevance. Play is undoubtedly a key factor in stimulating children from their earliest years of school, allowing them to acquire both academic knowledge and socio-emotional skills, which will form the basis for their well-rounded development.